Responses of concrete-filled cold-formed square hollow and double-C steel stub columns under cyclic and repeated loadings - Chayanon Hansapinyo (2018)
This paper presents an experimental study on the response of 18 concrete-filled cold-formed square hollow and double-C steel stub columns under cyclic and repeated loading. The test parameters were (1) infilled materials, i.e. No fill, concrete infilled and mortar infilled columns (2) cross sectional shape and dimension. The effect of lips in double-c section as inside stiffeners is presented. The cyclic tested results indicate the infilled columns possess higher bearing capacity, especially infilled materials with higher strength and non-compact section columns. However, there is no different in ultimate tensile. Moreover, the infilled columns showed larger area under post-yield hysteretic loops leading to better seismic performance. Failure of columns was modified in which the failure mode was shifted from the in-outward local buckling into the outward manner, consequently resulted to higher bearing capacity. © (2011) Trans Tech Publications, Switzerland.